αvβ6-integrin targeted PET/CT imaging in pancreatic cancer patients using 68Ga-Trivehexin - Rehm, Jana; Winzer, Robert; Pretze, Marc; Müller, Juliane; Notni, Johannes; Hempel, Sebastian; Distler, Marius; Folprecht, Gunnar; Kotzerke, Jörg (Frontiers in Nuclear Medicine, 2024)
68 Ga-Trivehexin is a PET tracer targeting αvβ6-integrin, a transmembrane receptor that is frequently expressed by pancreatic cancer cells. This study aimed to determine the biokinetics, image contrast, and acquisition parameters for 68 Ga-Trivehexin PET imaging in pancreatic cancers.44 patients with pancreatic cancer underwent Trivehexin PET/CT between June 2021 and November 2022 (EK-242052023). Biokinetics and -distribution were extracted. Previous imaging follow-up imaging, and histological findings were used as reference standards. A one-way ANOVA test, followed by Tukey HSD post-hoc test was conducted. T-tests for subgroups  chemotherapy prior to PET were performed. Based on dynamic PET data (n = 11) recorded over 45 min, time-activity curves were generated.68 Ga-Trivehexin PET/CT detected 40 pancreatic cancers, SUVmax 12.6; range [5.1-30.8]; 39 liver metastases, SUVmax 7.9 [2.7-16.3]; 21 lymph node metastases, SUVmax 8.6 [2.5-15.0]; 17 peritoneal metastases, SUVmax 9.5 [4.0-16.9] and 14 other metastases, SUVmax 7.2 [2.9-13.1]. Tukey post-hoc analysis revealed significant differences for SUVmax in pancreatic cancer compared to SUVmax in liver metastases (4.74, 7.75]), for SUVmax in pancreatic cancer to SUVmax in lymph node metastasis (4.07, 95%-CI [0.47, 7. 67]), for tumor-to-liver ratio (TLR) of liver metastasis to TLR of pancreatic cancer (1.82, 95%-CI [0.83, 2.80]), for TLR of pancreatic cancer to TLR of peritoneal carcinomatoses (-1.88, 95%-CI [-3.15, -0.61]), and TLR of pancreatic cancer to TLR of pleural carcinomatosis (-2.79, 95%-CI [-5.42, -0.18]). When comparing subgroups  chemotherapy prior to PET, TLR of pancreatic cancers and TLR of peritoneal carcinomatoses were significantly different. At 45 min p.i., the highest tumor-to-backround (TBR) was observed.68 Ga-Trivehexin is suitable for imaging of αvβ6-integrin expression in pancreatic cancer due to its ability to distinguish primary carcinoma and metastases from background tissue.